ANALYZING STUDENTS’ ERRORS IN USING INFINITIVE IN WRITING PARAGRAPH - Istiqama Mangalia; Nur Qalbi; Junaid (Journal of Language Testing and Assessment, 2021)
The purpose of this research is to analyze the types of errors of the third semester students of English department at Muhammadiyah University of Makassar in using the infinitive and to find out the cause of the errors. In this study, the researcher used descriptive qualitative method in term of percentages. In collecting data, the researcher used writing test and interview as the research instrument. The result of this study to determine the types of errors of students in using infinitive showed that the total errors of the students in using infinitive were 63 errors. This error consists of two types of errors, namely omission and addition. In omission, there are 33 errors or 50, 77%, while in addition there are 30 errors or 46, 16%. As for the cause of the students’ errors in using infinitive, some students no not understand and do not even know what the infinitive means and the function of the infinitive.